2019
DOI: 10.1101/704965
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chemogenetic evidence that rapid neuronal de novo protein synthesis is required for consolidation of long-term memory

Abstract: 46Translational control of memory processes is a tightly regulated process where the coordinated interaction and 47 modulation of translation factors provides a permissive environment for protein synthesis during memory 48 formation. Existing methods used to block translation lack the spatiotemporal precision to investigate cell-49 specific contributions to consolidation of long-term memories. Here, we have developed a novel chemogenetic 50 mouse resource for cell type-specific and drug-inducible protein synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…We found that mice that received light treatment 30 minutes after training exhibited significantly lower levels of freezing during testing 24 hours later compared to all the control groups (4E-BP no light, mCherry light/ no light) (Fig 5c-e). These results are consistent with previous findings in the field regarding the temporal windows of de novo protein synthesis required for memory consolidation and show for the first time that eIF4E-mediated protein synthesis in excitatory neurons in the LA is required for threat memory consolidation 13,[32][33][34] .…”
Section: Light Activation Of Opto4e-bp In the La After Cued Threat Co...supporting
confidence: 93%
See 3 more Smart Citations
“…We found that mice that received light treatment 30 minutes after training exhibited significantly lower levels of freezing during testing 24 hours later compared to all the control groups (4E-BP no light, mCherry light/ no light) (Fig 5c-e). These results are consistent with previous findings in the field regarding the temporal windows of de novo protein synthesis required for memory consolidation and show for the first time that eIF4E-mediated protein synthesis in excitatory neurons in the LA is required for threat memory consolidation 13,[32][33][34] .…”
Section: Light Activation Of Opto4e-bp In the La After Cued Threat Co...supporting
confidence: 93%
“…We proceeded to test the AAV9-EF1a-DIO-Opto4EBP-mCherry viral construct in vivo. We utilized this Opto4E-BP tool to determine temporal windows in excitatory neurons in the LA that require eIF4E-dependent protein synthesis for associative threat memory consolidation [32][33][34] . CamK2α.…”
Section: Light Activation Of Opto4e-bp In the La After Cued Threat Co...mentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, ISR activation by manipulations that promote eIF2-P abundance impairs long-term memory formation: hippocampal or basolateral amygdala injection of Sal003 (65,66), or pharmacogenetic activation of PKR in the hippocampus, impairs long-term memory in both rodents and birds (111,(115)(116)(117)(118).…”
Section: The Isr Is a Molecular Rheostat During Long-term Memory Formationmentioning
confidence: 97%